The impact of the objective state and self-esteem of health on academic performance in senior students of medical and humanitarian specialties, taking into account various environmental factors - V. V. Kuznetsov; K. V. Kosilov (Исследования и практика в медицине)
Purpose of the study. The goal is to conduct a comparative analysis of the correlation of learning success with self-assessment of physical and mental status and objective health status, taking into account the influence of demographic and socio-economic variables in senior students of medical and humanitarian specialties Materials and methods. The study was conducted from 01.12. 2017 to 01.03.2019 at the Far Eastern Federal University and the Pacific State Medical University. The sample size was 410 students (207 (50.6%) female, 203 (49.4%) male, average age 21.5 (1.2) years), who at the time of the study were studying in 4–6 courses. Information on demographic parameters, social conditions of study, residence, subjective data on morbidity and appeal was collected using: a comprehensive questionnaire on student status of a university (Pozdeeva, 2008; with additions of authors). The objective state of health and the comorbidity index were investigated when studying the medical documentation of medical institutions attached: Form 025 / y; 001–1 / y; 062 / y. In the study of quality of life associated with health, we used the international questionnaire “A short form of self-assessment of quality of life related to health MOS SF-36”. Results. The total score of self-esteem of physical well-being among students of humanities was 66.1 points, among students of medical specialties 56.4 points. Academic performance was higher among students of both directions, marking their learning conditions as satisfactory and good (r = 0.034; r = 0.048 / r = 0.045; r = 0.065). Student performance was also higher for students in both areas, evaluating the quality of education as high (r = 0.032; r = 0.046 / r = 0.033; r = 0.043), but lower for students with a high comorbidity index (r = –0.038 / r = –0.036). We also found that an increase in the number of HRQoL points is accompanied by a significant increase in academic performance in students of both directions (r = 0.035; r = 0.045 / r = 0.033; r = 0.050). An analysis of the linear regression model describing the association of academic performance with variables in the pooled sample revealed that this indicator strongly correlates with the comorbidity index (r = 8.27), HRQoL (r = 7.28), quality of education, and family income (5.55 / 5.06). At the same time, academic performance had an unreliable relationship with age, individual income, and weakly correlated with the conditions of study and residence. Conclusion. Chronic morbidity among senior medical and humanitarian students is high (comorbidity index 1.5–1.7), but the total self-assessment of the quality of life associated with health is 59–62 points and falls within the normal range of values. Thus, despite the high level of chronic somatic pathology, students generally positively assess their physical and psychological status.